2020
DOI: 10.3357/amhp.5618.2020
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Underpinnings of Emotional Conflict Control in Pilots

Abstract: BACKGROUND: Piloting an aircraft is a complex cognitive task. Human error represents a major contributing factor in aviation accidents. Emotion plays an important role in aviation safety. We performed a functional magnetic resonance imaging (fMRI) study to explore whether pilots and nonpilots may differ in the neural mechanisms responsible for the processing of conflict emotional information.METHODS: A total of 27 civil aviation pilots and 24 nonpilot controls performed the emotional Stroop task, in which par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Steinhauser et al (2016) found that the emotional conflict adaptation effect was only present if the previous response conflict was low; however, no overall effect was established. Jiang et al (2020), Hua et al (2021), Gold et al (2015), and Krug and Carter (2012) did not find a significant conflict adaptation effect in reaction time outcome measures. In contrast, Jarcho et al (2013), Irmen et al (2017), Chechko et al (2014), O.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Steinhauser et al (2016) found that the emotional conflict adaptation effect was only present if the previous response conflict was low; however, no overall effect was established. Jiang et al (2020), Hua et al (2021), Gold et al (2015), and Krug and Carter (2012) did not find a significant conflict adaptation effect in reaction time outcome measures. In contrast, Jarcho et al (2013), Irmen et al (2017), Chechko et al (2014), O.…”
Section: Resultsmentioning
confidence: 70%
“…Jiang et al (2020),Hua et al (2021),Gold et al (2015), andKrug and Carter (2012) did not find a significant conflict adaptation effect in reaction time outcome measures. In contrast, Jarcho et al (2013), Irmen et al (2017), Chechko et al (2014), O. J. Robinson et al (2011), A. Robinson et al (2015), Favre et al (2015), Maier and di Pellegrino (2012), Kar et al (2018), and Jeong and Cho (2021) reported a significant emotional conflict adaptation (resolution for Favre et al and Jeong and Cho) effect in behavioral response time data, however, Jeong and Cho only found this effect in low anxiety individuals in a safe context.…”
mentioning
confidence: 71%
“…Gao and Kong 15 conducted a study of personality types among Australian college students and found that pilot students in that sample had lower Neuroticism scores than non-pilot peers, a noticeable benefit for a role often requiring the ability to manage high stress effectively. Additionally, a recent neurological study indicated that the neural mechanisms for handling emotional conflict differ between pilots and non-pilots with the former showing higher emotional stability than the general population, as might be expected from a profession that requires affective control and focus 17 .…”
Section: Introductionmentioning
confidence: 99%